2020
DOI: 10.1001/jamacardio.2020.1445
|View full text |Cite
|
Sign up to set email alerts
|

Development of Persistent Opioid Use After Cardiac Surgery

Abstract: IMPORTANCEThe overuse of opioids for acute pain management has led to an epidemic of persistent opioid use.OBJECTIVE To determine the proportion of opioid-naive patients who develop persistent opioid use after cardiac surgery and investigate the association between the initial amount of opioids prescribed at discharge and the likelihood of developing new persistent opioid use. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study used data from a national administrative claims database from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 15 publications
4
124
1
1
Order By: Relevance
“…They found persistent use (defined as refilling an opioid prescription with 90 or 180 days postoperatively) in 10.2% of patients undergoing CABG and 8.1% of patients undergoing valve surgery. 45 Consistent with other studies on the development of chronic postsurgical pain, 46,47 persistent opioid use was more likely in younger female patients and patients with prior history of chronic pain, alcohol abuse, depression, drug use, and benzodiazepine use. The key finding from this study was that there was a direct association of MMEs prescribed at discharge with persistent opioid use.…”
Section: Pain and Cardiac Surgery Less Is Moresupporting
confidence: 88%
“…They found persistent use (defined as refilling an opioid prescription with 90 or 180 days postoperatively) in 10.2% of patients undergoing CABG and 8.1% of patients undergoing valve surgery. 45 Consistent with other studies on the development of chronic postsurgical pain, 46,47 persistent opioid use was more likely in younger female patients and patients with prior history of chronic pain, alcohol abuse, depression, drug use, and benzodiazepine use. The key finding from this study was that there was a direct association of MMEs prescribed at discharge with persistent opioid use.…”
Section: Pain and Cardiac Surgery Less Is Moresupporting
confidence: 88%
“…Specific surgical procedures that have been linked to an increased risk of persistent postoperative opioid use include total knee arthroplasty, simple mastectomy, open cholecystectomy, open appendectomy, cesarean delivery, and cardiothoracic surgery [ 6 , 10 ]. Additionally, many studies have shown that the amount and duration of opioids prescribed at discharge contribute to the development of new persistent postoperative opioid use [ 4 , 5 , 10 , 11 ••]. Knowledge of these risk factors can aid in the early identification of patients at high risk, which may significantly alter a patient’s trajectory of care.…”
Section: Risk Factors For the Development Of New Persistent Postoperative Opioid Usementioning
confidence: 99%
“…There is some evidence to suggest that orthopedic patients receive the highest doses of opioids, 7 but most series concluded that cardiac surgery is at least among the most culpable surgical specialties. 8 With as many as one-in-ten cardiac patients still using opioids at 90 days, 9 this certainly outstrips the prevalence of 3% in all-comers to surgery. 10 Perspective and scale are important:…”
Section: Churchill Would Have Approvedmentioning
confidence: 99%